2013
DOI: 10.1021/ol403106e
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Oxidative Decarboxylative Couplings of Sulfoximines and Aryl Propiolic Acids

Abstract: A method has been developed for the preparation of N-alkynylated sulfoximines involving the copper-catalyzed decarboxylative coupling of sulfoximines with aryl propiolic acids. A range of substituents on both the sulfoximidoyl moiety and the aryl group of the propiolic acid were compatible with this reaction process to afford a series of sulfoximidoyl-functionalized alkynes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(28 citation statements)
references
References 46 publications
0
27
0
1
Order By: Relevance
“…[18c] Under the optimized reaction conditions,ah ost of alkyl amine nucleophiles and electron-poor aryl acetic acids can be decarboxylatively cross-coupled ( Figure 4). Both cyclic and acyclics econdary amines,i na ddition to primary amines, undergo benzylation in moderate to excellent yields (2,(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…[18c] Under the optimized reaction conditions,ah ost of alkyl amine nucleophiles and electron-poor aryl acetic acids can be decarboxylatively cross-coupled ( Figure 4). Both cyclic and acyclics econdary amines,i na ddition to primary amines, undergo benzylation in moderate to excellent yields (2,(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…[6c] Cu-catalyzed C(sp) À N decarboxylative alkynylation has been limited to weakly nucleophilic NH partners (carbamates,l actams,i ndoles, sulfoximines). [8] ForC (sp 3 )-carboxylate amination, reports are limited to decarboxylative condensation processes that ultimately generate C(sp 2 ) À Nu nits in arylquinazolines, [9] or intramolecular decarboxylative aminations that require picolyl amine directing groups. [10] Existing methods for intermolecular decarboxylative cross-coupling of carboxylic acids and NH nucleophiles to generate C(sp 3 )ÀNb onds require stoichiometric activation of the acid.…”
Section: Introductionmentioning
confidence: 99%
“…98,99 N-Alkynylated sulfoximines 29 are structurally related to ynamides and recent studies by Bolm and coworkers have shown their greater reactivity in various transformations. [100][101][102][103] In particular, in what concerns the chemistry covered here, these highly activated alkynes are prone to undergo the regioselective catalystfree addition of carboxylic acids under remarkably mild reaction conditions (even at -20 °C). As shown in Scheme 15, performing the reactions in THF at r.t., different enol esters 30 could be synthesized in moderate to gold yields, in only 1 h, and with excellent stereoselectivities.…”
Section: Metal-free Reactionsmentioning
confidence: 99%
“…7 Since then, significant progress has been made by us and other groups. 8 A variety of substrates have been successfully employed as coupling partners, such as benzyl halide, 9 C-H activated heteroarenes, 10 organoboranes, 11 amides, 12 and organophosphorus 13 and organosulfur 14 compounds. Very recently, we reported a decarboxylative coupling reaction with organosilane using a nickel catalyst, which provided the diaryl alkyne in moderate to good yields.…”
mentioning
confidence: 99%